Behavioral Intervention versus Pharmacotherapy or Their Combinations in the Management of Overactive Bladder Dysfunction - Khanh Tran; Robert M. Levin; Shaker A. Mousa (Advances in Urology)
Overactive bladder syndrome (OAB) refers to individuals with the following symptoms: urinary urgency, increased urinary frequency, and urge incontinence. These symptoms are not life threatening but can cause embarrassment and significantly impact quality of life. There are numerous treatment options for OAB, including behavioral therapy, traditional pharmacological therapy or a combination of the two. These options are considered the mainstay of treatment for OAB. We carried out a comprehensive systematic review of the available literature on the effectiveness of behavioral intervention, anticholinergic drugs, and their combination in the management of adults with overactive bladder, with emphasis on results from clinical trials and primary literature. Each treatment intervention is efficacious, and the choice should be based on the patient's severity of symptoms, tolerability, compliance and satisfaction with the treatment. Based on available literature, management of OAB using a combination of behavioral therapy and drug intervention is the most efficacious in terms of patient satisfaction, perceived improvement, and reduction of bladder symptoms. It is also the most practical and cost effective for optimal management of patients with OAB. Pharmacological treatment, in addition to behavioral therapy, remains important in the management of adults with OAB syndrome.